Pelaksanaan dan Evaluasi Kegiatan Pelatihan Penguatan Storytelling Produk Desa Wisata Dukuh Penaban, Kabupaten Karangasem - Dianasari, Dewa Ayu Made Lily; Suasapha, Anom Hery; Lilasari, Luh Nyoman Tri; Sukariyanto, I Gede Made; Aridayanti, Dewa Ayu Nyoman (Jurnal Pengabdian Kepada Masyarakat Makardhi, 2025)
This article discusses the implementation of Community Service (PKM) activities conducted by lecturers of the Tourism Destination Study Program (DEP) at Bali Tourism Polytechnic in Dukuh Penaban Tourism Village. The PKM activity, which focused on "Storytelling," aimed to enhance participants' understanding and skills in storytelling in English. The activity received positive feedback from participants, as evaluated through a survey based on 25 indicators of PKM implementation. The results indicated that all participants rated the activity as "Good." Notably, the quality of the presenters and the material delivered were highly rated across all indicators. The participants, consisting of both male and female individuals, shared similar views regarding the quality of the PKM activity. Based on the positive feedback, this article recommends that future PKM activities focus on refining and improving the identified areas to achieve even greater excellence.